Reestructuración y aplicación de un sistema contable en comercial Gsm World Connection, periodo: enero-marzo de 2013 - Minchala Morocho, Ruth Cecilia (2016)
This paper entitled "Restructuring and implementation of an accounting system in Commercial GSM World Connection, Period: January to March 2013, located in the province of Azuay, Cuenca Canton was prepared according to the rules and parameters set by the Regulation of Academic Regime the National University of Loja, meeting the requirements for obtaining engineering degree in Accounting and Auditing. Certified Public Auditor. Its development is welcomed: • Reporting Standards, • International Accounting Standards, • Organic Law on Internal Taxation and Regulation • Labour Code, • Social Security Act, among other laws and principles that you can apply for legal operation of a company. Main objective was established to implement the commercial accounting Comercial GSM World Connection, starting with the review and analysis of the source documents, which allowed for a brief diagnosis and registration of the initial inventory of its assets and liabilities, then made the Chart of Accounts according to the activities of the company, together with the relevant Manual, then the entire accounting process ending with the presentation of the financial statements was applied. Suggesting improve and implement the implanted so that its owner the right decisions take your accounting system.